Mechanism of deoxygenation in anisole decomposition over single-metal loaded HZSM-5: Experimental study - Zhang, Jiajun; Fidalgo, Beatriz; Kolios, Athanasios; Shen, Dekui; Gu, Sai (Elsevier, 2017)
This work investigates the deoxygenation reaction during the decomposition of anisole (methoxy-rich model compound of lignin) over bi-functional catalyst. The bi-functional catalyst consisted of a single metal loaded on an acid support; the active metals, i.e. Ni, Co, Mo and Cu, were loaded at various rates, and the acid support was HZSM-5 zeolite with a Si/Al ratio of 25 (HZ(25)). Experiments were conducted in a bench-scale fluidised bed reactor within the temperature range from 400°C to 600°C. Experimental results revealed that the increase in temperature and metal loading promoted the selectivity of BTX fraction. Nevertheless, a simultaneous increase in the yield of carbonaceous deposits was also observed at the expense of liquid fraction, both phenolics compounds (Phs) and aromatic hydrocarbons (AHs). 500°C was the preferred temperature for BTX production. Ni-loaded HZ(25) catalyst could dramatically facilitate the conversion of Phs to monoaromatics and increase the selectivity of BTX fraction by 43.4%; Mo-loaded HZ(25) catalyst exhibited the best catalytic activity towards the total production of AHs and promoted the BTX yield by 27.1%. It was also found that 1 wt.% was the optimum loading ratio for both Ni and Mo on HZ(25) to obtain the highest BTX yield and selectivity. Characterization of fresh bi-functional catalysts showed that micro polycrystalline metal sites, in the range of 4 -10 nm, existed on the fresh catalyst and exhibited strong interaction with the HZ(25) support. For the spent catalysts, large amount of amorphous carbonaceous deposit was observed, ascribed to the polycondensation of aromatic compounds during the reaction. Three reaction pathways were proposed for the catalytic deoxygenation of anisole, with the hydrogen being available in-situ as product of the polycondensation reactions
Keywords: Anisole; Catalytic decomposition; Deoxygenation; Bi-functional catalyst; BTX